Pengaruh Beban Kerja Terhadap Motivasi Tenaga Kerja Perawat di Rumah Sakit Muhammadiyah Bandung - Rohman, Erfa Saeh; Fitria, Ida Jalilah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of workload on nurse work motivation at Muhammadiyah Hospital Bandung. The phenomenon of high workload among nurses has become an urgent issue in healthcare services, where nurses as frontline healthcare workers experience pressure due to increasing patient numbers, administrative demands, and limited resources. This research employs a quantitative method with descriptive design. The research population consists of all nurses at Muhammadiyah Hospital Bandung totaling 130 people, with a sample of 57 respondents determined using Slovin's formula with a 10% margin of error. Data were collected through questionnaires measuring workload variables (high job demands and low job control) and work motivation (behavioral direction, effort level, and persistence level). Data analysis used simple linear regression with classical assumption tests including normality, autocorrelation, and heteroscedasticity tests. The results show that there is a positive and significant effect of workload on nurse work motivation with t-calculated > t-table (7.497 > 1.67303) and significance level 0.000 < 0.05. The correlation coefficient of 0.711 indicates a strong and positive relationship, while the coefficient of determination (R²) of 0.505 indicates that 50.5% of work motivation variation can be explained by workload.